PENGARUH DINAMIKA TIM VIRTUAL TERHADAP KINERJA ORGANISASI SYARIAH DENGAN STRATEGI OPTIMALISASI KERJA JARAK JAUH SEBAGAI MEDIASI DI BANK MUAMALAT, PADANG - Sarianti, Kiki; Rosalina, Desi; Desti, Yolanda; Damayanti, Nora; Ramadhi, Ramadhi; Amri, Andi; Azhari, Alim Bahri (Ekonomi Islam, 2024)
This study aims to analyze the impact of virtual team dynamics on organizational performance in sharia, with a remote work optimization strategy as a mediating variable at Bank Muamalat Padang City.  This study uses a quantitative approach by collecting data through a survey of employees who work in virtual teams in sharia economy-based organizations with a sample of 85 respondents. The analysis model used is structural equation modeling (SEM) to test the relationship between virtual team dynamics, organizational performance, and the moderation role of remote work optimization strategies. The results showed that collaboration and communication have a significant influence on Optimizing Remote Work Strategies, while trust has no significant effect on Optimizing Remote Work Strategies. Collaboration and communication have a significant influence on Organization Performance, while trust has no significant effect on Organization Performance. In addition, Optimizing Remote Work Strategies has not been shown to have a significant effect on Organization Performance. The results of the study show that Optimizing Remote Work Strategies does not mediate the influence of organizational performance trust, The results of the study show that Optimizing Remote Work Strategies can mediate the influence of Collaboration on Organization Performance and the results of the study show that Optimizing Remote Work Strategies cannot mediate the influence of Communication on Organization Performance. Keywords: Virtual Team Dynamics, Organization Performance, Optimizing Remote Work Strategies.